1996
DOI: 10.1111/j.1651-2227.1996.tb13919.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal iron status in maternal anemia

Abstract: Hemoglobin, serum iron, transferrin saturation and ferritin were measured on paired maternal and cord blood samples in 54 anemic (hemoglobin < 110 g/L) and 22 non-anemic (hemoglobin > or = 110 g/L) pregnant women at term gestation. The levels of hemoglobin, serum iron, transferrin saturation and ferritin were significantly low in the cord blood of anemic women, suggesting that iron supply to the fetus was reduced in maternal anemia. The linear relationships of these parameters with both maternal hemoglobin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
0
6

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 17 publications
6
53
0
6
Order By: Relevance
“…Extensive studies indicate that an increase in the expression of TfR in placental microvilli might be a result of a compensatory mechanism with regard to iron de®ciency and mild iron-de®ciency anemia in pregnant mothers (Huebers, 1990). However, the function of this compensatory system is believed to be limited based on the fact that the Tf saturation is remarkably decreased and the TfR expression is also hindered in pregnant women with severe iron de®ciency (Singla et al, 1996;Allen, 2000). In addition, it was reported that iron status in fetuses whose mothers were suffering from iron de®ciency is normal or nearly normal, being independent of maternal iron status (Gebre-Medhin & Birgegard, 1981;Dallman, 1989;Bhargava et al, 1991;Lao et al, 1991;Institute of Medicine, food and Nutrition Board, 1993;Hokama et al, 1996), although different results have been reported (Blot et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Extensive studies indicate that an increase in the expression of TfR in placental microvilli might be a result of a compensatory mechanism with regard to iron de®ciency and mild iron-de®ciency anemia in pregnant mothers (Huebers, 1990). However, the function of this compensatory system is believed to be limited based on the fact that the Tf saturation is remarkably decreased and the TfR expression is also hindered in pregnant women with severe iron de®ciency (Singla et al, 1996;Allen, 2000). In addition, it was reported that iron status in fetuses whose mothers were suffering from iron de®ciency is normal or nearly normal, being independent of maternal iron status (Gebre-Medhin & Birgegard, 1981;Dallman, 1989;Bhargava et al, 1991;Lao et al, 1991;Institute of Medicine, food and Nutrition Board, 1993;Hokama et al, 1996), although different results have been reported (Blot et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported (Finch et al, 1983) that low levels of plasma iron, as found in severe iron de®ciency, could result in damage to fetal tissues and reduced capacity of placental tissues to take up iron. Singla et al (1996) demonstrated that a mild degree of maternal anemia has little in¯uence on iron accretion in the fetus. However, with increasing severity of maternal anemia, the fetus accumulates less and less iron, and levels of serum iron, Tf saturation and ferritin in the cord blood of severely anemic women is markedly decreased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15][16][17] In a multivariate regression analysis of data from 691 women in rural Nepal, adjusted decrements in neonatal weight of 38, 91, 187, and 153 g were associated with haemoglobin concentrations ≥ 20 90-109, 70-89 and < 70 g/L, respectively. A significant fall in birth weight due to increase in prematurity rate and intrauterine growth retardation has been reported when maternal haemoglobin levels were below 8.0 g/dl.…”
Section: Maternal Anaemia and Birth Weightmentioning
confidence: 99%
“…It has generally been considered that maternal Fe de®ciency during pregnancy has little effect on fetal, neonatal and infant Fe status because of preferential transfer of Fe from the mother to the fetus (Rios et al 1975;Morton et al 1988;Hussain et al 1997). Extreme maternal Fe de®ciency as occurs in developing countries may be an exception (Singla et al 1996). This view is now challenged by two prospective studies from Spain (Colomer et al 1990) and Jordan (Kilbride et al 1999), that have demonstrated a clear relationship between anaemia in pregnancy and anaemia in the infant at 1 year old.…”
Section: Iron Status During Early Infancymentioning
confidence: 99%